God on the hill : temple poems from Tirupati - Annamācārya, 1408-1503 (Oxford University Press, 2005)
The devotional poems of Annamaya (15th century) are perhaps the most accessible and universal achievement of classical Telugu literature, one of the major literatures of pre-modern India. This book offers translations of 150 of Annamaya's poems, which are readable as poetry in their own right.